2013
DOI: 10.1590/s2197-00252013000100007
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and chemical elicitation of defense oleoresin production in field-grown slash pine under subtropical climate

Abstract: Oleoresin is a key defense strategy of advanced gymnosperms, based on the combination of a complex anatomical structure of resin ducts and elaborate terpene biochemistry. Given the vast array of oleoresin economic applications in the chemical, pharmaceutical, agrochemical, and biofuel industries, translating factors that regulate terpene biosynthesis into higher oleoresin yield is a challenge for the forestry industry. Field tests with approximately 3,500 28-year-old slash pine (Pinus elliottii Engelm. var. el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Although chemical stimulant pastes have been intensely studied in Pinus elliottii Engelm var. elliottii (slash pine) aiming at higher yields of oleoresin (Rodrigues et al, 2008 , 2011 ; Rodrigues and Fett-Neto, 2009 ; Rodrigues-Corrêa and Fett-Neto, 2013 ), knowledge of genes and their regulatory pattern for terpene biosynthesis in commercial forests are still unknown. Acquiring this information would be a crucial aspect to understand the biochemical and physiological basis of oleoresin production.…”
Section: Introductionmentioning
confidence: 99%
“…Although chemical stimulant pastes have been intensely studied in Pinus elliottii Engelm var. elliottii (slash pine) aiming at higher yields of oleoresin (Rodrigues et al, 2008 , 2011 ; Rodrigues and Fett-Neto, 2009 ; Rodrigues-Corrêa and Fett-Neto, 2013 ), knowledge of genes and their regulatory pattern for terpene biosynthesis in commercial forests are still unknown. Acquiring this information would be a crucial aspect to understand the biochemical and physiological basis of oleoresin production.…”
Section: Introductionmentioning
confidence: 99%
“…How to reduce the cost of pastes and achieve a similar promoting effect is important for the popularization and application of resin-stimulant pastes. Previous studies indicated that it was possible to replace commercial resin-stimulant pastes containing CEPA with the pastes containing potassium ions in P. elliottii 9 , 16 . Our study showed that there was no significant difference in total resin yield between the K 2 SO 4 and CEPA treatment groups, while the resin yield of the treatment group with NAA or BA was lower than that of the CEPA treatment group in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Auxin is another molecule that can promote ethylene biosynthesis and resin canal differentiation. Metal cofactors of terpene synthases, such as iron or potassium ions, are also used as replacements for CEPA 16 . It is known that either auxin (2,4-dichlorophenoxyacetic acid, 2,4-D) or salicylic acid have a similar effect to CEPA on increasing resin production 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…var. elliottii revealed its seasonal variation [17]. The highest yield of oleoresin was observed from the tapped trees during summer.…”
Section: Introductionmentioning
confidence: 94%